The Effect of Incentives and Work Environment on Civil Service Performance and Job Satisfaction as Intervening Variables - Siti Hardiyanti Waris; Mahlia Muis; Musran Munizu (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
This study aimed to determine the Effect of Incentives and Work Environment on Civil Service Performance and Job Satisfaction as Intervening Variables in Disperkimtan. South Sulawesi. The method in this study was a descriptive method with a quantitative approach with the aim to determine the effect of the variables studied. The population in this study were all Civil Servants covered by Disperkimtan Sulsel, amounting to 135 people. While the sample used in this study amounted to 134 people. Data collection techniques using survey methods through observation, questionnaires, and literature study. Data analysis was performed using SPSS ( Statistical Package for the Social Science) version 25. The results of this study indicated that direct incentives and work environment have a positive and significant effect on job satisfaction and employee performance in Disperkimtan South Sulawesi. There was no positive and significant effect between incentives on performance through job satisfaction as an intervening variable. While job satisfaction as an intervening variable that mediates between work environment and performance has no positive and significant effect. In this case, job satisfaction weakened the influence of the work environment on the performance of civil servants.